Rekonstruksi Identitas Diri Mahasiswa Melalui Partisipasi dalam Kewirausahaan di HIPMI PT UNNES - Caharani, Fatin; Fatimah, Nurul (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Student participation in campus-based entrepreneurship organizations is not only related to the development of business skills but also serves as an important space for students to reinterpret their roles an identities. Campus entrepreneurship organizations provide a social environment that brings together academic experiences, business practices, and collective interactions that shape students understanding of entrepreneurship. This study aims to analyze the process of entrepreneurial identity reconstruction among students through active participation in HIPMI PT UNNES. The research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with members and administrators of HIPMI PT UNNES, as well as non-participant observation of organizational activities represented through content on the HIPMI PT UNNES Instagram account. Research participants were selected using purposive sampling, and the data were analyzed thematically. The findings indicate that HIPMI PT UNNES functions as a social transitional space that enables students to experience gradual changes in self-meaning. The identity reconstruction process is characterized by role ambiguity between academic and entrepreneurial identities, social uncertainty, and the negotiation of identity meanings through social interactions within the organization. Over time, some students begin to internalize entrepreneurial values such as independence, risk-taking, and action orientation. Drawing on Turner’s concept of liminality and Mead’s symbolic interactionism, this study finds that entrepreneurial identity reconstruction is a dynamic and non-linear social process. This study contributes to a deeper understanding of campus entrepreneurship organizations as strategic arenas for student identity formation, not only as spaces for business learning but also as social environments for entrepreneurial identity development.